Prescribing medicines in pregnancy. (July 2016) - Yates, Laura M.; Thomas, Simon H.L.
Abstract: Prescribing in pregnancy is complex; it needs to take into account the effects that physiological changes associated with pregnancy can have on a drug's pharmacology and the impact of these changes on the benefits and risks of treatment in the mother, as well as the benefits and risks to the developing fetus. Fetal effects are sometimes predictable, given the mechanism of action of a drug, but they can be unpredictable and unexpected. Identifying therapies that are safest for the fetus, yet do not compromise effective treatment of the maternal condition, is essential but challenging. Whereas older drugs may have been used in pregnancy without any signal of fetal harm, often little is known about the fetal risk of newer preparations, which may be preferred for the mother due to improved efficacy or adverse effect profiles. Some drugs essential for the management of long-term maternal conditions are known to have teratogenic properties and there may be no effective alternatives. Weighing up the risks and benefits for mother and fetus in such circumstances is particularly difficult. Teratology information services are established worldwide and provide up-to-date, evidence-based advice to support informed prescribing in pregnancy. Information designed for use by pregnant women is also increasingly available to help inform their choices.